Juridical Review of the Criminal Process Against Children as Offenders After the Age Of 18 Based on the Indonesian Penal System - Diamond Wulandari Badja; Kaharuddin Shah; Mohamad Didi Permana (Program Pascasarjana Universitas Muhammadiyah Palu, 2025)
This study aims to analyze and determine the legal status for children who commit criminal acts that are processed by the court at the age of 18 years and to analyze and find out the criminal law arrangements in the juvenile justice process that are carried out after the perpetrator (child) is 18 years old. The research method used is normative legal research using a legislative approach and a conceptual approach, The data source in this study comes from secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials which are analyzed qualitatively and then draw conclusions using a deductive thinking process. The results of this study are: 1). In the juvenile justice process that is carried out after the perpetrator (child) is 18 years old, the legal position still refers to the age at which the crime was committed (tempus delicti). This reinforces the principle that juvenile criminal law is retroactive to a certain age limit; 2). The juvenile justice process that is carried out after the perpetrator (child) is 18 years old is still based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.